2005
DOI: 10.1128/jvi.79.18.11705-11715.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase Activity of Influenza A Virus in an Endocytic Pathway Enhances Viral Replication

Abstract: In contrast, the enzymatic activities of WSN/Unstable-NAs, the replication of which had no effect on pretreatment with zanamivir, were undetectable in cells under the same conditions. Hemadsorption assays of transfectant-virus-infected cells revealed that the low-pH stability of the sialidase had no effect on the process of removal of sialic acid from hemagglutinin in the Golgi regions. Moreover, high titers of viruses were recovered from the lungs of mice infected with WSN/Stable-NAs on day 3 after intranasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 35 publications
2
67
0
5
Order By: Relevance
“…30) Recently, sialidase activity of influenza virus sialidase has been reported to function not only in the late stage but also in the initial stage of virus infection cycles, indicating that viral sialidase activity in late endosome/lysosome traffic on cell entry facilitates production of infectious progeny viruses from the infected cells. 31) The results indicate that GH has effects not only in the late stage of IAV infection, such as the assembly and budding of progeny viruses, but also in the early stage, such as virus entry process via the endocytic pathway.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…30) Recently, sialidase activity of influenza virus sialidase has been reported to function not only in the late stage but also in the initial stage of virus infection cycles, indicating that viral sialidase activity in late endosome/lysosome traffic on cell entry facilitates production of infectious progeny viruses from the infected cells. 31) The results indicate that GH has effects not only in the late stage of IAV infection, such as the assembly and budding of progeny viruses, but also in the early stage, such as virus entry process via the endocytic pathway.…”
Section: Resultsmentioning
confidence: 88%
“…32,33) The low-pH stability of IAV sialidase is functionally linked to virus entry via the endocytic pathway and contributes to the ability of virus replication. 31) The difference of GH effects between A/Aichi/2/68 (H3N2) and other strains may depend on the low-pH stability of their sialidase activities.…”
Section: Resultsmentioning
confidence: 99%
“…The sialidase activity has been suggested to be involved in enhancement of virus infection and replication at the early stage of the virus lifecycle such as virus attachment to the host cellular surface and cell entry process, but the mechanism remains unknown. [4][5][6][7] We have found that influenza A virus also showed strong binding to a non-sialo glycoconjugate, sulfatide 8) (Fig. 1).…”
Section: Introductionmentioning
confidence: 84%
“…The low-pH stability of NA conferred by 344R and 466F was reported to increase the replication ability of a virus in the MDCK cell line [38]. KBNP-0028 possessed the amino acids associated with the low pH stability, and the high productivity may be attributed to the low pH stability, in part.…”
Section: Discussionmentioning
confidence: 99%